Determinants of Household Consumption in Indonesia 2018-2020 - Rani Wahlian Aru Munjayanah; P. Eko Prasetyo (Efficient: Indonesian Journal of Development Economics, 2024)
Growth in household consumption in Indonesia has tended to decline over the past few years, which can disrupt Indonesia's economic growth. This study aims to analyze the effect of layoffs, income, population and home ownership on household consumption in Indonesia. The research method used is the 2018-2020 panel data regression model with the FEM technique. The results of this study indicate that the variables of layoffs and income have an effect on household consumption in Indonesia. Meanwhile, the variables number of population and percentage of own home ownership have no effect on household consumption in Indonesia. The coefficient of determination is 0.982772, meaning that the variables of layoffs, wages, population and PKRS can simultaneously explain 98.27% of household consumption, while the remaining 1.73% is explained by other variables outside the model. There needs to be special attention from the Government regarding the large number of layoff cases, providing assistance in the form of capital assistance funds, equal access to job training programs for all people, especially those of productive age, to reduce the impact of layoffs which then does not cause permanent unemployment.